Penguatan Kapasitas Manajemen Pengetahuan UMKM Kerajinan Pandai Besi Tradisional di Desa Mekarmaju - Indiyati, Dian; Ramadhani, Dian Puteri; Mulyawan, Irwan (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2026)
Mekarmaju Village in Bandung Regency is a center for traditional blacksmithing, with hundreds of craftsmen producing various metal products with a turnover of nine billion rupiah per month. However, most of this expertise is still tacit and at risk of being lost as the generations change. The community service program on 15 July 2025 provided knowledge management training to 52 participants, including craftsmen, village officials, and residents involved in the blacksmithing ecosystem. During the 30-minute session, participants were introduced to the basic concepts of knowledge management, the difference between tacit and explicit knowledge, and the importance of systematic documentation. The assessment results showed an increase in participants' understanding, with the average score rising from 64.1 to 86.5 and the completion rate from 57% to 83%. The satisfaction evaluation recorded very positive responses (average 3.69 out of 4.00). The program also highlighted sustainability challenges, as younger generations tend to choose other professions, although some university graduates showed interest in contributing through design innovation and digital marketing. Practically, this training plays an important role in preserving traditional blacksmithing knowledge and supporting the continuity of local culture.